To Be or Not to Be: The Case of Endoplasmic Reticulum Aminopeptidase 2 - Kuśnierczyk, Piotr (Frontiers in Immunology, 2022)
To be, or not to be, that is the question. (William Shakespeare, Hamlet) Endoplasmic reticulum aminopeptidases 1 and 2 (ERAP1 and ERAP2, respectively) play a role in trimming peptides that are too long to be bound and presented by class I HLA (HLA-I) molecules to CD8+ T cells. They may also affect the HLA-I-presented peptide repertoire by overtrimming potential epitopes. Both enzymes may also be released from the cell to cleave cytokine receptors and regulate blood pressure. Both enzymes are polymorphic, which affects their expression, specificity, and activity, resulting in their role in diseases associated with HLA-I. In this brief review, we concentrate on ERAP2, less investigated because of its lack in laboratory mice and 25% of humans, as well as a lower polymorphism. ERAP2 was found to be associated with several diseases and to influence ERAP1 effects. It was discovered recently that the defective ERAP2 gene, not encoding functional aminopeptidase, may nevertheless, during viral infections, produce a truncated protein isoform of unknown function, possibly interfering with ERAP1 and full-length ERAP2 by heterodimer formation. The disease associations of ERAP2, alone or in combination with ERAP1, are reviewed.